EFEKTIFITAS ASUHAN KEPERAWATAN DENGAN TERAPI MANDI AIR HANGAT DALAM MENGATASI GANGGUAN POLA TIDUR PADA LANSIA - Eltrikanawati T. (Jurnal Ilmiah Cerebral Medika, 2021)
Everyone has a sleep-wake cycle that is usually done to determine when the right time to sleep. This time can be supported by light or sun during the day, eating habits and activities carried out as usual at certain times of the day. A person who has a sleep-wake pattern that shows more sleep quality and better performance than a person who has a changing sleep pattern. The purpose of implementing this care is to be able to overcome sleep pattern disorders experienced by the elderly with hypertension. The method used is a case study conducted based on the stages of care, including assessment, diagnosis, intervention, implementation and evaluation. The results of care by giving warm water therapy for six days showed that there was an increase in sleep time for one hour, when compared to the previous sleep. It is hoped that the elderly can apply this non-pharmacological therapy, one of which is the application of warm bath therapy in overcoming sleep pattern disorders. Key words: Sleep Pattern Disorders, Warm Bath Therapy, Elderly